Muscadine grapes (Vitis rotundifolia) and dealcoholized muscadine wine alleviated symptoms of colitis and protected against dysbiosis in mice exposed to dextran sulfate sodium. (February 2020) - Li, Ruiqi; Wang, Gary P.; Whitlock, Joan A.; Zhao, Shaomin; Yagiz, Yavuz; Gu, Liwei
Graphical abstract: Highlights: Diets supplemented with muscadine grape or wine alleviated symptoms of colitis in mice. Fecal content of acetic acid and butyric acid in colitis mice were increased by muscadine grape or wine. Muscadine grape or wine partially corrected gut dysbiosis in colitis mice. Abstract: The objective of this study was to investigate the effects of freeze-dried muscadine grapes (FMG) or dealcoholized muscadine wine (DMW) on the symptoms and gut microbiota in mice with chronic colitis. C57BL/6J mice (female, 6-weeks old) were fed a control diet, control diet supplemented with FMG (7%, w/w) or DMW (5.5%, v/w). After 28 days, chronic colitis was induced by 3% DSS in drinking water for 7 days. FMG or DMW significantly reduced weight loss and other symptoms of chronic colitis ( P ≤ 0.05). FMG or DMW increased fecal content of acetic acid and butyric acid in mice exposed to DSS. DSS treatment caused drastic dysbiosis in colon which were significantly improved by FMG and DMW in diet. DMW decreased the relative abundance of Clostridium and Akkermansia but increased the abundance of Roseburia, Anaerotruncus, and Coprococcus . This study suggested that muscadine gape or wine alleviate murine colitis and their activities were associated with reduced dysbiosis in colon.